A new species of the genus Mongolotettix Rehn, 1928 from Heilongjiang, China (Orthoptera, Acridoidea, Acrididae) - Zhang, Xiaohong; Yin, Hong (Zootaxa, 2020)
A new species of the genus Mongolotettix Rehn, 1928 i.e. Mongolotettix moheensis sp. nov is described from Jiangsu, China. The new species is allied to M. zhengi Li et Lian, 1994, but differs tegmina of male longer, almost almost reaching the base of epiproct, maximum width of cubital area 2.5 times maximum width of medial area, width of epiphallus equal to high, fulculae smaller and interspace of mesosternum narrowed in the middle slightly. Type specimens are deposited in the Natural Museum of Hebei University, Baoding, Hebei, China.